2022
DOI: 10.3748/wjg.v28.i29.3917
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of microRNA as a biomarker for the diagnosis of hepatocellular carcinoma

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Current guidelines for HCC management recommend surveillance of high-risk patients every 6 mo using ultrasonography. Serum biomarkers, like alpha-fetoprotein (AFP), protein induced by vitamin K absence/antagonist-II (PIVKA-II) and lectin-reactive AFP, show suboptimal performance for detection of HCC, which is crucial for successful resection or treatment. Thus, there is a significant need for new biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…For instance, Fang et al [51] suggested that a combination of miR-16, miR-122 and the protein alpha-fetoprotein could increase AUC to 0.862. On the other hand, and in concordance with our results, Malik et al [28] showed that adding miRNAs to the protein biomarkers AFP or DCP did not improve the diagnostic performance further. These results reflect the diverging roles of miRNAs in the diagnosis of HCC, indicating that further research is needed.…”
Section: Auc For Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, Fang et al [51] suggested that a combination of miR-16, miR-122 and the protein alpha-fetoprotein could increase AUC to 0.862. On the other hand, and in concordance with our results, Malik et al [28] showed that adding miRNAs to the protein biomarkers AFP or DCP did not improve the diagnostic performance further. These results reflect the diverging roles of miRNAs in the diagnosis of HCC, indicating that further research is needed.…”
Section: Auc For Parameterssupporting
confidence: 92%
“…Furthermore, many miRNAs may be both up-and down-regulated in HCC patients, which could lead to analytical difficulties in clinical practice. However, a small number are reported to be upregulated in HCC patients in more than a few publications, the most common of which are miR-21 [11,15,23,[26][27][28], miR-29 [22,26,[29][30][31], miR-192 [11,15,30], miR-199 [15,31,32], miR-221 [26,33,34], miR-222 [26,34], and miR-224 [18,32,35]. Of four meta-analyses that evaluated the diagnostic value of miRNAs for HCC detection, three cautiously encouraged their role as biomarkers [27,36,37], whereas one concluded that adding miRNA to the protein biomarkers AFP or DCP did not improve the diagnostic performance [28].…”
Section: Introductionmentioning
confidence: 99%
“…Blood hsa-miRs are of interest for the research of illness prognosis and the detection of cancer due to their great stability in blood and other liquid biopsy samples [ 38 ]. In the current study, combining each of the investigated miRs individually to AFP ROC curve analysis yielded an improved AUC each time compared to either alone.…”
Section: Discussionmentioning
confidence: 99%
“…During the ROC curve analysis, we decided to increase AFP cutoff to 23.3 ng/mL to ensure the inclusion of AFP-negative HCC cases (12/39) [ 32 ]. However, Malik et al [ 38 ] stated that hsa-miR-21-5p alone or in combination with AFP did not improve the diagnostic performance of the protein biomarkers. Moreover, we thought to investigate miRs’ fold change ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenes and tumour suppressor genes are both dysregulated during the complicated aetiology of HCC [35][36][37] . By controlling tumour suppressor genes, miRNAs have been shown to be crucial in the development of tumours 38 .…”
Section: Discussionmentioning
confidence: 99%